2012
DOI: 10.1590/s0100-29452012000200041
|View full text |Cite
|
Sign up to set email alerts
|

Composição de ácidos graxos em polpa de frutas nativas do cerrado

Abstract: Dentre as fruteiras do Cerrado brasileiro com forte potencial para a exploração sustentada, encontram-se o araticum (Annona Crassiflora Mart.), o coquinho-azedo (Butia Capitata Mart.) e o pequi (Caryocar Brasiliense Camb.). O objetivo deste trabalho foi caracterizar o teor de óleo e o perfil de ésteres metílicos da fração lipídica da polpa dos frutos destas três espécies. Os teores de lipídeos foram determinados por extração contínua a quente com éter de petróleo em extrator tipo Soxhlet. O óleo para perfil de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
3
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 5 publications
2
18
3
9
Order By: Relevance
“…Lopes et al (2012) found 66% of oleic acid; 0.24% of vaccemic acid and 0.23% of palmitoleic acid in Annona coriacea pulp oil, therefore, with percentages different from the results of this study. Unsaturated fatty acids with the lowest percentage were cyclopropane-octanoic acid (8:0), with 0.2 and 0.2%, and 9,12-octadecadienoic acid (18:Δ 9,12 ), known as linoleic acid, with 0.2 and 0.2%.…”
Section: Chemical Componentcontrasting
confidence: 99%
See 4 more Smart Citations
“…Lopes et al (2012) found 66% of oleic acid; 0.24% of vaccemic acid and 0.23% of palmitoleic acid in Annona coriacea pulp oil, therefore, with percentages different from the results of this study. Unsaturated fatty acids with the lowest percentage were cyclopropane-octanoic acid (8:0), with 0.2 and 0.2%, and 9,12-octadecadienoic acid (18:Δ 9,12 ), known as linoleic acid, with 0.2 and 0.2%.…”
Section: Chemical Componentcontrasting
confidence: 99%
“…The percentage of saturated fatty acids was 33.5 and 34.2%, resulting from the physical and chemical extraction, respectively. Lopes et al (2012) reported a percentage of unsaturated fatty acids of 29.7% in araticum pulp oil, lower than that of this study. The major saturated fatty acids in atemoya seed oil, resulting from chemical and physical extractions, respectively, were hexadecanoic acid (16:0), with 15.0 and 13.4%, known as palmitic acid; octadecenoic acid (18:0), with 14.1 and 14.5%, known as stearic acid.…”
Section: Chemical Componentcontrasting
confidence: 95%
See 3 more Smart Citations